Severe Neonatal Epileptic Encephalopathy and KCNQ2 Mutation: Neuropathological Substrate? - Dalen Meurs-van der Schoor, Charlotte; van Weissenbruch, Mirjam; van Kempen, Marjan; Bugiani, Marianna; Aronica, Eleonora; Ronner, Hanneke; Vermeulen, R. Jeroen (Frontiers in Pediatrics, 2014)
Background: Neonatal convulsions are clinical manifestations in a heterogeneous group of disorders with different etiology and outcome. They are attributed to several genetic causes. Methods: We describe a patient with intractable neonatal seizures who died from respiratory compromise during a status epilepticus. Results: This case report provides EEG, MRI, genetic analysis and neuropathological data. Genetic analysis revealed a de novo heterozygous missense mutation in the KCNQ2 gene, which encodes a subunit of a voltage-gated potassium channel. KCNQ2 gene mutation is associated with intractable neonatal seizures. EEG, MRI data as well as mutation analysis have been described in other KCNQ2 cases. Postmortem neuropathologic investigation revealed mild malformation of cortical development with increased heterotopic neurons in the deep white matter compared to an age-matched control subject. The new finding of this study is the combination of a KCNQ2 mutation and the cortical abnormalities. Conclusions: KCNQ2 mutations should be considered in neonates with refractory epilepsy of unknown cause. The mild cortical malformation is an important new finding, though it remains unknown whether these cortical abnormalities are due to the KCNQ2 mutation or are secondary to the refractory seizures.